1995
DOI: 10.1007/bfb0053426
|View full text |Cite
|
Sign up to set email alerts
|

Can D.S.A. be improved? — Complexity trade-offs with the digital signature standard —

Abstract: :The Digital Signature Algorithm (DSA) was l~Oposed in 1991 by the US National Institute of Standards and Technology to provide an appropriate core fur applications requiring digital signatures. Undoubtedly, many applications will include this standard in the future and thus, the foreseen domination of DSA as a legal certification tool is sufficiently important to focus research endeavours on the suitebility of this scheme to various sitnatic~s.In this paper, we prcsant s~x new DSA-based protocols for :9 Perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
105
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 5 publications
0
105
0
1
Order By: Relevance
“…A batch verification algorithm is used to determine whether a set of signatures contain invalid ones. In 2008, considering that the verification of massive messages may induces huge time cost in mobile networks, Yu et al proposed an efficient identity-based batch verification scheme to reduce the delay in network coding [6]. Zhang et al [7] discussed a batch signature verification scheme for the communications between vehicles and infrastructure to lower the total verification time.…”
Section: IImentioning
confidence: 99%
See 2 more Smart Citations
“…A batch verification algorithm is used to determine whether a set of signatures contain invalid ones. In 2008, considering that the verification of massive messages may induces huge time cost in mobile networks, Yu et al proposed an efficient identity-based batch verification scheme to reduce the delay in network coding [6]. Zhang et al [7] discussed a batch signature verification scheme for the communications between vehicles and infrastructure to lower the total verification time.…”
Section: IImentioning
confidence: 99%
“…Lee et al [7] proposed a method to identify bad signatures in RSA-type batches. Later, Law and Matt [6] presented the quick binary and exponentiation method, to find invalid signatures in the pairing based signature schemes. Stanek [7] showed that method was flawed, and proposed an improved protocol to ©IJRASET (UGC Approved Journal): All Rights are Reserved resist attacks.…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…Batch verification, which is firstly introduced by Naccache et al [40], is used to verify multiple signatures simultaneously consuming less time than verifying total individual signatures. Successive research results have achieved improvements in terms of efficiency and security [1,3,4,5,8,9,21,27,51].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, all members of a group of users may share some fixed number of bits of their RSA moduli, or users may want to include a binary representation of their personal data in their RSA modulus. For DSA keys with a predetermined portion see [13].…”
Section: Introductionmentioning
confidence: 99%